Toward a Decolonial Creative Writing Workshop: Mbari as a Case Study in Examining Intercultural Models for Arts Education - James W Ryan; Steve Westbrook (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
The creative writing workshop has been the subject of sustained critique for its tendency to reproduce dominant cultural norms, especially in spaces where admissions to the workshop do not reflect local ethnic and cultural diversity. In an effort to aid the search for alternate models/foundations for creative writing instructions, the authors turn to the history of mbari, a cultural practice among the Owerri Igbo of Nigeria, which was briefly adapted into the pedagogical foundation for a visual arts workshop conducted between the time of Nigeria’s independence and the onset of its civil war. In its original form, mbari was a sacred, collective arts ritual through which practitioners cemented social bonds among diverse groups within the local community. In its later adaptation as pedagogy, mbari became an effort to produce “authentic” local art in a global marketplace. This essay examines the values and local social norms that made mbari so vital for the Owerri Igbo and then teases out cautionary lessons from the appropriation of mbari as a workshop pedagogy. The authors argue that, by examining the successes and failures of previous efforts to adopt “non-western” arts practices into workshop pedagogies, instructors and pedagogues can be more mindful about their efforts to reform the creative writing workshop.
Keywords: JAEPL